Opportunistic bacteria confer the ability to ferment prebiotic starch in the adult cystic fibrosis gut - Wang, Y.; Leong, L.E.X.; Keating, R.L.; Kanno, T.; Abell, G.C.J.; Mobegi, Fredrick; Choo, J.M.; Wesselingh, S.L.; Mason, A.J.; Burr, L.D.; Rogers, G.B. (TAYLOR & FRANCIS INC, 2019)
Chronic disruption of the intestinal microbiota in adult cystic fibrosis (CF) patients is associated with local and systemic inflammation, and has been linked to the risk of serious comorbidities. Supplementation with high amylose maize starch (HAMS) might provide clinical benefit by promoting commensal bacteria and the biosynthesis of immunomodulatory metabolites. However, whether the disrupted CF gut microbiota has the capacity to utilise these substrates is not known. We combined metagenomic sequencing, in vitro fermentation, amplicon sequencing, and metabolomics to define the characteristics of the faecal microbiota in adult CF patients and assess HAMS fermentation capacity. Compared to healthy controls, the faecal metagenome of adult CF patients had reduced bacterial diversity and prevalence of commensal fermentative clades. In vitro fermentation models seeded with CF faecal slurries exhibited reduced acetate levels compared to healthy control reactions, but comparable levels of butyrate and propionate. While the commensal genus Faecalibacterium was strongly associated with short chain fatty acid (SCFA) production by healthy microbiota, it was displaced in this role by Clostridium sensu stricto 1 in the microbiota of CF patients. A subset of CF reactions exhibited enterococcal overgrowth, resulting in lactate accumulation and reduced SCFA biosynthesis. The addition of healthy microbiota to CF faecal slurries failed to displace predominant CF taxa, or substantially influence metabolite biosynthesis. Despite significant microbiota disruption, the adult CF gut microbiota retains the capacity to exploit HAMS. Our findings highlight the potential for taxa associated with the altered CF gut microbiotato mediate prebiotic effects in microbial systems subject to ongoing perturbation, irrespective of the depletion of common commensal clades.